CYSTATIN C: AN IMPROVED ESTIMATOR OF MODERATELY IMPAIRED GLOMERULAR FILTRATION RATE - CHITRA Y. DHUME,; NANDINI K. PADTE,; SUNANDA AMONKAR,; SAGAR BADACHI,; MAYA JIRAGE,; ANUPAMA KUNKOLIENKAR, (International Journal of Pharma and Bio Sciences, 2012)
Diabetic nephropathy1-2 is a clinical syndrome characterised by persistent albuminuria (>300mg/24hr), a decrease in glomerular filtration rate (GFR), raised arterial blood pressure and enhanced cardio vascular morbidity and mortality. It is an important micro vascular complication of long standing non insulin-dependent diabetes mellitus (NIDDM) as well as insulin dependent diabetes mellitus (IDDM).Initially there is hyper filtration which declines to return to a normal at approximately 10years3,4 . After 10 years there is sustained proteinuria and by 14years it reaches the nephritic range. Detection of diabetic nephropathy as early in the disease process as possible currently offers the best chance of delaying or possibly preventing progression to end stage disease5.Screening for microalbuminuria and proteinuria in a structured, regular manner is recommended3,4.The present study was conducted to detect the correlation between Glomerular filtration rate determined by creatinine clearance and serum Creatinine, serum Urea, Urea clearance, Cockcroft Gaolt formula, MDRD formula, Cystatin C and Microalbuminuria in diabetic patients with nephropathy and to study the correlation between glomerular filtration rates in diabetic patients at various levels of glomerular filtration rate and to compare ability of various parameters to detect mildly impaired (70-90ml/min) glomerular filtration rate.